An Empirical Analysis of the Impact of Boko-Haram Activities on Budgeting Processes in Nigeria - Julius Adavize Adinoyi; Martin Odhiambo Ouma; Mumo Nzau (Richtmann Publishing, 2023)
Countries faced with terrorism in Africa cannot adequately check, advocate, and enable the delivery of public financial management (PFM). The activities of Boko-Haram in Northeastern Nigeria have disrupted public activities and affected key stakeholders’ involvement in the budget process, availability of budgeting information and budget performance. This study interrogates the impact of Boko-Haram on budgeting transparency and accountability. The research design was informed by interviews and documented studies. A diagnostic test was conducted on variables to confirm their reliability, validity and normality. Likert scale was used to find out the opinions of the respondents. Descriptive and inferential analysis was adopted in this research. With a significant regression model (p-value <0.05), the analysis shows that terrorism accounts for 89.28% variation in budget performance. The authors noted fewer scholarly efforts to interrogate how terrorism undermines budgeting as an aspect of PFM in economic governance. Hence recommends more research in this subject area, particularly in other terror affected countries in Africa. This paper recommends increased policy support by enhancing public accessibility of budget documents, engendering consultative forums for citizens' participation in the budget process in secure locations, and timely budgetary reports and audits by relevant government agencies. Received: 17 April 2023 / Accepted: 30 June 2023 / Published: 5 July 2023